Adrenomedullin is a useful biomarker for the prognosis of critically ill septic children. (October 2014) - Jordan, Iolanda; Corniero, Patricia; Balaguer, Mònica; Ortiz, Jessica; Vila, David; Velasco, Jesús; Cambra, Francisco J; Esteban, Elisabeth
Aim: To measure midregional pro-adrenomedullin (MR-pro-ADM) in critically ill septic patients to determine its prognostic usefulness as compared with other used biomarkers in pediatric intensive care units, C-reactive protein (CRP) and procalcitonin (PCT).Materials & methods: Prospective observational study conducted on 95 patients.Results: Mean levels of MR-pro-ADM were significantly higher when patients needed mechanical ventilation (3.2 ± 4.3 vs 1.6 ± 2.4) and inotropes (4.4 ± 5.2 vs 1.3 ± 1.2). Receiver operating characteristic curves of mortality were higher for MR-pro-ADM (cut-off value of 2.2). This marker showed higher positive predictive prognostic value than PCT and CRP (31 vs 21.6% and 15.8%, respectively).Conclusion: MR-pro-ADM levels are good indicators of disease severity and show better reliability than PCT and CRP for predicting in-hospital mortality.